The Figurative Language Analysis in “The Chronicles of Narnia: The Last Battle, Book 7” by C. S. Lewis - Marpaung, Marlin Steffi (LPPM Universitas Advent Indonesia, 2025)
Figurative language aids the reader in understanding the author's goals in addition to making the material more entertaining to read. The following research questions will be addressed by this study by identifying the figurative language techniques and the interpretation of each figure of speech in the book The Chronicles of Narnia: The Last Battle: Book 7. The following questions were addressed by this study: 1) What is the figure of resemblance or relationship used in the novel; 2) What is the figure of emphasis or understatement found from the novel? 3) What is the figure of sounds found in the novel; and 4) How many imageries are found in the novel The Chronicles of Narnia: The Last Battle Book 7 and the meaning? The research methodology used in this study is qualitative descriptive. The data are gathered by the researcher through data collecting from a range of books and library research. Based on the results, there is the figure of resemblance or relationship with 23 kennings, 4 personifications, and 12 synecdoche; the figure of emphasis or understatement with 5 paradoxes and the explanation of the climax; the figure of sounds with 35 onomatopoeias, 74 repetitions, assonance with repetition of the o͞o (u) sound, repetition of the ou sound, repetition of the ā (ei) sound, repetition of the i long sound, repetition of the ə sound, repetition of the ē (i) sound, and repetition of the ai sound; and 17 imageries. The most common use of figurative language categories is the figure of sounds with 35 onomatopoeias and 75 repetitions.